Consolidation Coefficient in Horizontal Direction (Ch) Determined from Field Settlement Data By Using Terzaghi, Asaoka, and Finite Element Methods - Lastiasih, Yudhi; Mochtar, Noor Endah; Nasya, Farah (IPTEK Journal of Proceedings Series, 2017)
In order to predict the consolidation period in the field, consolidation coefficient in vertical direction (Cv) parameter is needed. When vertical drains installed in the compressible layer in order to shortened the consolidation period, it needs consolidation coefficient in horizontal direction (Ch). This Ch parameter has to be determined from the field settlement that usually obtained from the trial embankment.Â  However, it is very expensive to carry out the trial embankment; therefore, it is usually assumed to be 2 till 5xCv. In this paper, the assumption of the Ch value will be proven by using field settlement data taken from the trial embankment at the reclamation area for container yard at Kuala Tanjung, Medan, By choosing the Ch value, the compression vs time curves were predicted by adopting the Terzaghi, Asaoka, and Finite Element methods. Afterwards, these predicted settlement curves were plotted with the field settlement curves; from this plotting, it could be figured out the predicted curves which has Ch value the same with the field Ch value. The results show that from three methods adopted in this study, only the Terzaghi and the Asaoka methods give satisfactory results in settlement prediction. Consequently, only the Terzaghi and Asaoka methods are adopted to determine the Ch value. The Ch value obtained is about the same, that is 3Cv until 5Cv. When that Ch value used back to predict the settlement, the Asaoka method gives better result than the Terzaghi method.